(untitled) (Eurasian Scientific Herald, 2022)
The article reveals the process of using multimedia technologies and results in teaching foreign languages. Effective methods are analyzed that lead to a clear perception of information in a foreign language. This article also discusses a motivational approach for the effective achievement of the goal.